Assessment of Bioequivalence Using Urinary Excretion Data: A Review - Troja, Eva; Deda , Leonard (Pharmaceutical Research - Recent Advances and Trends Vol. 2, 2024)
The present study highlights about assessment of bioequivalence using urinary excretion data. A rapid method for assessing the bioavailability of a drug is the use of urinary excretion data. This method is based on the principle that the urinary excretion rate of an unchanged drug is directly proportional to the plasma concentration of the drug. So, bioavailability can be calculated as the ratio of the total amount of unchanged drug in urine after administration of the test (T) and reference (R) formulations. Urine metabolite excretion data are not used to assess bioavailability since the drug undergoes metabolism in the body, anatomically and the rate of metabolism may vary for different reasons. This method applies to drugs that are excreted unchanged in the urine, e.g., some thiazide diuretics, sulfonamides, biguanides and drugs that act on the urinary tract, such as urinary antiseptics (nitrofurantoin and hexamine). It is concluded from this study that the formulations Glucophage and Metformin (tablets 850 mg) exhibit a similar elimination rate, which indicates a similarity in their bioavailability and bioequivalence. Based on this study, some drugs such as metformin can therefore be evaluated to simulate and predict absorption through urinary excretion data. Due to the high invasiveness of bioequivalence/bioavailability conventional studies, the prediction of absorption can be performed using the urinary excretion method. Furthermore, the urinary excretion methodology represents low costs, it is a less invasive method, and its throughput is viable when compared to the conventional method with blood samples.